2018
DOI: 10.1016/j.jbiomech.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of elastic, viscoelastic and failure tensile material properties of knee ligaments and patellar tendon

Abstract: The knee ligaments and patellar tendon function in concert with each other and other joint tissues, and are adapted to their specific physiological function via geometry and material properties. However, it is not well known how the viscoelastic and quasi-static material properties compare between the ligaments. The purpose of this study was to characterize and compare these material properties between the knee ligaments and patellar tendon. Dumbbell-shaped tensile test samples were cut from bovine knee ligame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 58 publications
2
44
0
Order By: Relevance
“…The grips allowed free motion of the ligament, except for the axial direction ( i.e., rotation and translation perpendicular to the axial loading direction). Specimens were preloaded to 10N to reduce slackness and their initial length was measured (using the image data from the DIC method), followed by a preconditioning step of 10 cycles of axial stretching to 5% at a frequency of 1 Hz ( Ristaniemi et al, 2017 ). Axial stretching was accomplished by displacement driven elongation of the initial measured length of the ligament.…”
Section: Methodsmentioning
confidence: 99%
“…The grips allowed free motion of the ligament, except for the axial direction ( i.e., rotation and translation perpendicular to the axial loading direction). Specimens were preloaded to 10N to reduce slackness and their initial length was measured (using the image data from the DIC method), followed by a preconditioning step of 10 cycles of axial stretching to 5% at a frequency of 1 Hz ( Ristaniemi et al, 2017 ). Axial stretching was accomplished by displacement driven elongation of the initial measured length of the ligament.…”
Section: Methodsmentioning
confidence: 99%
“…∂ ∂γ The set of nonlinear equations (14) and its derivatives (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were discretized by the standard finite element method [1], resulting in the residual vector and the tangent matrix of the classical Newton-Raphson algorithm, respectively. An analogous discretization procedure is presented in Carniel et al [7], where one can find further technical details regarding the numerical implementation.…”
Section: Appendix: Linearizationsmentioning
confidence: 99%
“…Tensile tests are widely applied to assess the mechanical behavior of a broad range of composite materials. Particularly for biological fibrous tissues-such as tendons, ligaments, and arteries-tensile tests comprise the main experimental approach to study their mechanical responses [9,17,29]. In this case, the hypothesis of a homogeneous uniaxial stress state could be assumed in some regions of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of viscoelastic characteristics including strain rate dependency, hysteresis, creep and stress relaxation has been observed consistently in soft biological tissues such as the sclera (Elsheikh et al, 2010;Geraghty et al, 2020), cornea (Elsheikh et al, 2011;Kazaili et al, 2019), and tendon (Robinson et al, 2004;Zuskov et al, 2020). Similarly, ligaments inherit non-linear viscoelastic characteristics exhibiting both elastic and viscous behaviour, hence they are history-and time-dependent (Bonner et al, 2015;Fung, 1993;Ristaniemi et al, 2018). The initial part of the non-linear load-deformation behaviour in ligaments is the toe region where the wavy collagen fibres become taut and straighten as load is applied, hence the crimp is removed (Fratzl et al, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…However, a study on rabbit medial collateral ligament complexes at varying strain rates (between 0.66 and 9300 %/min) showed that the ligaments were only minimally strain rate dependent (Woo et al, 1990b(Woo et al, , 1981. The small effect of strain rate stiffening could be because the studies combined stress-strain characteristics at the toe region with the elastic region (Haut and Little, 1969;Ristaniemi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%